2014
DOI: 10.1371/journal.pone.0097812
|View full text |Cite
|
Sign up to set email alerts
|

The Scaling of Host Density with Richness Affects the Direction, Shape, and Detectability of Diversity-Disease Relationships

Abstract: Pathogen transmission responds differently to host richness and abundance, two unique components of host diversity. However, the heated debate around whether biodiversity generally increases or decreases disease has not considered the relationships between host richness and abundance that may exist in natural systems. Here we use a multi-species model to study how the scaling of total host community abundance with species richness mediates diversity-disease relationships. For pathogens with density-dependent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
116
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(120 citation statements)
references
References 33 publications
4
116
0
Order By: Relevance
“…Moreover, whether diversity inhibits transmission and subsequent disease risk often depends strongly on the type of transmission involved (e.g., density‐dependent or density‐independent) as well as whether communities assemble additively or substitutively (i.e., does total host abundance increase with diversity or remain constant? ; Dobson, ; Johnson, Ostfeld, et al., ; Mihaljevic, Joseph, Orlofske, & Paull, ). Further research would be required to investigate these points specifically for ranaviruses, as well as to obtain more high‐resolution estimates of infection over time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whether diversity inhibits transmission and subsequent disease risk often depends strongly on the type of transmission involved (e.g., density‐dependent or density‐independent) as well as whether communities assemble additively or substitutively (i.e., does total host abundance increase with diversity or remain constant? ; Dobson, ; Johnson, Ostfeld, et al., ; Mihaljevic, Joseph, Orlofske, & Paull, ). Further research would be required to investigate these points specifically for ranaviruses, as well as to obtain more high‐resolution estimates of infection over time.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting how total transmission among all hosts should change with host diversity may be less clear if contact rate is a non-linear function of host density [4]. For example, some trematodes release more cercariae infective stages when their current first intermediate hosts are in the presence of more second intermediate hosts [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have deliberately avoided providing quantitative results, as doing so would be claiming a false accuracy. We also remind readers that additive and substitutive host changes lie at extremes of a continuum and that disease outcomes in complex communities are unlikely to follow simple rules (e.g., Roche et al 2013;Mihaljevic et al 2014). Our results have, however, clearly demonstrated that modeling FD transmission without explicitly considering the vector can limit model applicability to real-world VBD systems.…”
Section: Discussionmentioning
confidence: 83%
“…In our pair of models, additive host change and FD transmission causes amplification of DIV (under certain combinations of transmission success and host recovery probabilities). Previous models have suggested that amplification ought not to occur when transmission is FD, even when the host change is additive (Rudolf and Antonovics 2005;Mihaljevic et al 2014). Indeed, if one considers only PIH (the prevalence of infection in hosts), it does not (note that the NR3 scenario is not strictly FD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation